Determination of the Complex Composition by the Method of Isomolar Series - Ubaydullayeva Saidaxon Baxromjon qizi; Jumaboyev Alisher G’ofurovich (Genius Journals, 2022)
This paper describes experimental methods for the separation of nickel ions from the adsorbent using dimethylglyoxime in the regeneration of adsorbents.
Keywords: Ni; ions; activated carbon adsorbent; spent MDEA solution